Ultrafast excited state relaxation dynamics in a heteroleptic Ir(iii) complex, fac-Ir(ppy)2(ppz), revealed by femtosecond X-ray transient absorption spectroscopy. Issue 12 (13th April 2021) - Choi, Jungkweon; Ahn, Mina; Lee, Jae Hyuk; Ahn, Doo-Sik; Ki, Hosung; Oh, Inhwan; Ahn, Chi Woo; Choi, Eun Hyuk; Lee, Yunbeom; Lee, Seonggon; Kim, Jungmin; Cho, Dae Won; et al.
Abstract : The experimental and calculation results demonstrate that the  3 MLppz CT state generated by the spin-forbidden transition rapidly relaxes to  3 MLppy CT through internal conversion process with a time constant of ∼450 fs. Abstract : A typical metal complex has a central metal surrounded by multiple ligands, which greatly affect the properties of the whole complex. Although heteroleptic complexes often exhibit substantially different behaviors from homoleptic complexes, systematic studies to explain their origins have been rare. Of special importance is to understand why the heteroleptic metal complex shows a more complicated excited state relaxation dynamics than the homoleptic metal complex. To address this issue, we investigated the excited state relaxation dynamics of a heteroleptic Ir(iii ) complex, fac -Ir(ppy)2 (ppz), and two homoleptic Ir(iii ) complexes, fac -Ir(ppy)3 and fac -Ir(ppz)3, using femtosecond X-ray transient absorption (fs-XTA) spectroscopy, ultrafast optical transient absorption (TA) spectroscopy, and DFT/TDDFT calculation. The data show that the ultrafast relaxation dynamics of ∼450 fs, which is significantly faster than those of previous Ir(iii ) complexes with other ligands, is observed only in fac -Ir(ppy)2 (ppz) but not in the homoleptic Ir(iii ) complexes. Such dynamics observed for only heteroleptic Ir(iii ) complexes must originate from the heteroleptic character, and naturally, the inter-ligand energy transfer between two different types of ligands has been suggested to explain the fast dynamics. Both fs-XTA and TA data, however, favor the assignment of the ultrafast dynamics of ∼450 fs to the internal conversion (IC) process from the ppz-localized 3 MLCT to the ppy-localized 3 MLCT. The DFT/TDDFT calculations support that the abnormally fast IC for fac -Ir(ppy)2 (ppz) is due to a large nonadiabatic coupling and the small energy gap between the two states.